INTEGRATION OF MODERATE ISLAMIC VALUES IN CHARACTER EDUCATION AT ANAK SALEH ELEMENTARY SCHOOL MALANG - Retno Sugiarti; Ozay, Mehmet (The Islamic Education and Multiculturalism Foundation, 2022)
Abstract: Islam carried main mission to improving human morals, not only teachings of monotheism and worship, but also concepts and guidelines in one's interaction as a pluralistic world citizen exemplified by Prophet Muhammad SAW. Islam recognizes differences in beliefs, cultures, traditions, races, and certain tribes, one of them is stated in Q.S Al-Hujurat: 13 about diversity. However, not everyone agrees with this point of view, emergence of various sects in Islam, such as extremism who have an exclusive, closed, and intolerant perspective also affects development of Islamic religion.It is undeniable that these intolerant, radical, and other attitudes can enter into every line of our lives, including in world of education. As one of efforts to prevent extremism/radicalism in institution of education is the integration of moderate Islamic values ​​in character building in elementary schools. One of elementary schools that has tried to integrate these values ​​is SD Anak Saleh. This study uses a qualitative approach with type of case study design. The results showed that: 1) moderate Islamic values ​​were applied in character education through Panca Character program at SD Anak Saleh. 2) The strategy is applied in learning at class (intracurricular), outside class (co-curricular) and in extracurricular activities by inculcating five characters, namely personal, social, natural, intellectual, and national character. 3) Implication of implementation of Panca Character is that most of graduates from SD Anak Saleh have moderate attitudes, such as tolerant, religious (used to carry out mandatory and sunnah worship), inclusive, social care, and love for Indonesian homeland.